1990
DOI: 10.1136/pgmj.66.778.684
|View full text |Cite
|
Sign up to set email alerts
|

Large bowel obstruction due to an impacted barolith—a delayed complication of a barium study

Abstract: Complications of barium sulphate studies abound in the literature but there are very few recorded instances of large bowel obstruction due to inspissated barium and faeces forming a 'barolith'. A patient who suffered this complication is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Constipation is the most common symptom that patients present after a barium study. The interval between a barium study and symptomatic manifestation of barolith may range from 2 days to 2 years …”
Section: Discussionmentioning
confidence: 99%
“…Constipation is the most common symptom that patients present after a barium study. The interval between a barium study and symptomatic manifestation of barolith may range from 2 days to 2 years …”
Section: Discussionmentioning
confidence: 99%
“…In this review 24 articles [7–30] describing 34 cases were initially identified. However two articles were excluded; one described two cases in which a barium examination had converted a partial obstruction to a complete obstruction and therefore did not represent barolith‐induced obstruction as such [10].…”
Section: Literature Searchmentioning
confidence: 99%
“…The size of the barolith was only reported in five cases and all of these were similar in size. The smallest reported barolith was 4 × 2 cm [18] and the largest was >6 cm [12].…”
Section: Site and Size Of Barium Obstructionmentioning
confidence: 99%
See 2 more Smart Citations